Migration And Mobility In Britain Since The Eighteenth Century - Pooley, Colin (Taylor & Francis, 1998)
Poplulation migration is one of the demographic and social processes which have structured the British economy and society over the last 250 years. It affects individuals, families, communities, places, economic and social structures and governments. This book examines the pattern and process of migration in Britain over the last three centuries. Using late 1990s research and data, the authors have shed light on migrations patterns including internal migration and movement overseas, its impact on social and economic change, and highlights differences by gender, age, family, position, socio-economic status and other variables.